IW Financial Expert Survey: Second Quarter 2020 - Markus Demary; Stefan Hasenclever (Institut der deutschen Wirtschaft (IW), 2020)
Pessimism related to the outbreak of the Coronavirus Disease 2019 and its development in 2020 determines the experts' predictions for the second and third quarter of 2020. The pessimistic outlook can be inferred from the downward revisions of the experts' forecasts. More downward revisions than upward revisions for almost all indicators illustrate that the survey participants assume that the corona crisis will plunge the economy into recession over the next two quarters. Consequently, all experts have revised their growth outlooks for Germany and the Euro Area downwards. The same applies for the prediction of Germany's and the Eurozone's inflation rates with one exception. At a first glance, it may seem counterintuitive that the subdued inflation and growth outlooks associated with the corona crisis are not reflected in the experts' short-term interest rates forecasts as most experts revised these upwards. Obviously, this is related to the previous pessimistic projections of the short-term rate after it has plunged in September 2019 as a reaction to the ECB's cut of the deposit rate to -0.5 percent. Though, most of the experts expect the short-term to rise but the projected rates are still lower than the current rate at the end of March 2020. These projections cover the forecasters expected path of monetary policy. Following the corona crisis, the FED has cut the FED Funds Rate aggressively so that both the FED Funds rate and the EZB main policy rate have been at their effective lower bound at the end of March. Most experts predict that neither the ECB nor the FED will adjust their short-term policy rate during the second quarter of 2020. Hence, the main policy instrument of these cen-tral banks is expected to remain accommodative. The participants still expect the yield curve to become flatter. The lower average forecasts for the short-term interest rate are consistent with the experts' lower inflation and growth expec-tations. For 2020, the experts expect 0.7 percent inflation in the Eurozone and a growth rate of real gross domestic product of -4.9 percent, which indicates a plunge of economic growth and a failure of the European Central Bank (ECB) to meet its inflation target. Given that, the fore-casters have lowered their outlook for the long-term interest rate to -0.57 percent at the end of the second quarter of 2020. The yield on US Treasury bonds with 10-years maturity is expected to increase slightly from 0.67 percent at the end of March 2020 to 0.76 percent by the end of the second quarter 2020. In the light of the global flight to safety in government debt due to the outbreak of the corona crisis, the US long-term rate has hit a new low in March 2020. The Fed-eral Funds Rate is anticipated to remain at 0.00-0.25 percent, i.e. its effective lower bound. The increase in demand for safety assets together with the investors' needs to raise cash for debt repayments denominated in USD have been leading to an appreciation of the USD in the first quarter 2020. Until the end of the second quarter, the participants predict a small depreciation of the US-Dollar against the Euro from 1.103 Euros at the end of the first quarter 2020 to 1.096 Euros at the end of the second quarter 2020...
Keywords: G12; G17; 330; Wirtschaftsprognose; Zins; Prognose; Deutschland; Eurozone